1972
DOI: 10.1139/z72-220
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the activities of two purified fish gonadotropins on adenyl cyclase activity in the goldfish ovary

Abstract: The pituitary gonadotropin from a Pacific salmon (Oncorhynchus tshawytscha) stimulates adenyl cyclase activity in homogenates of ovaries from goldfish (Carassius auratus) but it is about 36 times less active than carp (Cyprinus carpio) gonadotropin. Moreover, a higher maximal stimulation of the cyclase is obtained with the more homologous (carp) gonadotropin. These results suggest the existence of a partial zoological specificity of teleost gonadotropins in their stimulating action on adenyl cyclase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…GtH has been shown to stimulate adenyl-cyclase activity in immature fish ovary (Fontaine et al 1972;Idler et al 1975) and we recently demonstrated an intrafollicular peak of cAMP after adding GtH in incubation of trout isolated follicles at 'P-GV' stage (A. Fostier, B. Jalabert, B. Finet, unpublished data). In addition, in vitro 17~,20/3-OH-P production by isolated follicles of amago salmon was enhanced by db-cAMP (Young et al 1983c).…”
Section: Discussionmentioning
confidence: 82%
“…GtH has been shown to stimulate adenyl-cyclase activity in immature fish ovary (Fontaine et al 1972;Idler et al 1975) and we recently demonstrated an intrafollicular peak of cAMP after adding GtH in incubation of trout isolated follicles at 'P-GV' stage (A. Fostier, B. Jalabert, B. Finet, unpublished data). In addition, in vitro 17~,20/3-OH-P production by isolated follicles of amago salmon was enhanced by db-cAMP (Young et al 1983c).…”
Section: Discussionmentioning
confidence: 82%
“…In fish, gonadotropin (GTH) stimulates the production of maturational steroid by the follicle wall, and this process is mediated by adenylyl cyclase (Fontaine et al, 1972;Fostier et al, 1983;Nagahama et al, 1985a). Therefore, phosphodiesterase inhibitors or adenylyl cyclase stimulators potentially could elevate CAMP levels in the follicle wall as well as in the oocytes themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The (Fontaine et al, 1970 ;Menon and Smith, 1971 ;Fontaine et a/., 1972 (Tsafriri et al, 1972a, b), luteinization (Channing, 1970 ;Kolena and Channing, 1971), ovarian steroidogenesis (Pharrissetof., 1968 ;Speroff and Ramwell,1970 ;and (normal light cycle) ; the other timed the onset of the light phase at 6 p.m., and therefore reversed the conditions (reversed light cycle). At the end of the acclimation period, the oocytes developed beyond a mean diameter of 600 g, at which stage they are known to be effectively responsive to SG-G100 (Kuo et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, piscine pituitary gonadotropins were shown to be effective in teleost systems, although they showed a specificity among teleosts (Breton et al, 1973). Species specificity within teleosts was reported to be minor compared with that between teleost and mammalian species (Fontaine et al, 1972 (Labhsetwar, 1975). Okamura et al (1972), Jalabert and Szollosi (1975), and Jalabert (1976) …”
Section: Introductionmentioning
confidence: 99%